Perbandingan Kapasitas Dukung Aksial Pondasi Tiang Tunggal Dengan Beberapa Metode Analisis (Studi Kasus : Pondasi Rumah sakit Pendidikan Universitas Riau Pekanbaru) - Sanjaya, Gigih; Satibi, Syawal; Muhardi, Muhardi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
A pile foundation design should be done carefully and as carefully as possible. Each foundation must be able to support loads up to the limit safely, including supporting the maximum load that may occur. The purpose of this study was to determine the bearing capacity and settlement of pile foundation at Rumah Sakit Pendidikan Universitas Riau Pekanbaru Project. Analyses were performed by static and dynamic methods to determine the bearing capacity of piles and settlement. Bearing capacity of piles with static methods is calculated based on the data field (SPT) and laboratory while the method of dynamically calculated based on the field data is data obtained static load test and Pile Driving Analyzer (PDA) while driving operation. In this paper, we describe briefly how the calculate bearing capacity of the pile vertical for some methods such as Meyerhof, Poulus dan Davis, U.S Army Corps, Briaud et al. (1985), Metode β, Software All Pile and From the analysis data , ultimate bearing capacity vertical for single pile base on SPT and laboratory methods Briaud et al. (1985) is near ultimate bearing capacity for single pile base on static load test Keywords: SPT, Pile Driving Analyzer (PDA), static load test and bearing capacity,